Study of the Ātmā [Soul] in Sanskrit and Nepali Literature - Pokhrel, GovindaPrasad (Rupantaran: A Multidisciplinary Journal, 2022)
This research article entitled A Study of Ātmā [Soul] as God in Sanskrit and Nepali Literature deals with the general concept of the Ātmā[Soul] which is called God too. The research questions are what is Ātmā and how it exists in the body of the organisms. The researcher mentions the following objectives for this study: 1.to define the Ātmā [Soul] 2.to study how it exists in the body of the organisms. This research follows qualitative method. Descriptive, comparative and deductive methodology is used in it. Nepali and some Sanskrit literary figures are studied in it and the researcher mentions how far they have gone to study about the Soul in their works. The literary figures have pointed out about the sense in the living beings and this sense is called psyche, Soul, Consciousness etc.The researcher also tries to show the universal Soul and its grandeur. Soul is called God because it is immortal and wide.